Splendors of the Gonzaga Catalogue: Exhibition 4 Nov. 1981 - 31 Jan. 1982, London - David Chambers; Jane Martineau (Cinisello B.mo A. Pizzi, 1981)
Ill.
Gonzaga - Arte
Edizioni San Paolo srl - Piazza Soncino, 5 - 20092 CINISELLO BALSAMO (MI) (non commercial uses only) ® Copyright 2018